Generic web-based survey system generator / Tan Chin Teng - Tan, Chin Teng (2007)
Survey is one of the important research methods and is popularly used by the researchers. The increased usage of the Internet and the World Wide Web technologies has provided opportunities for web-based surveys. The purpose of this dissertation is to study the current usage of the web-based survey as the selected survey method and to produce a generic web-based survey generator to help the researchers improve the process of constructing web-based surveys. The main idea of web-based survey generator is to simplify the process of constructing the web-based surveys where the web-based survey forms can be generated automatically. With the web-based survey generator, the researchers are able to produce and deploy web-based surveys more efficiently. Feedback from the survey can be stored in a database and basic reports are generated automatically. Data can be easily imported into web page or report file for more comprehensive reporting. Hence, to achieve the purpose of this dissertation, a prototype of web-based survey generator had been developed through this study.